The Effect of Blended Learning and Instagram Media Towards Students’ Writing Skill - Faujiah, Winda Oktavia; Mardiah, Mardiah (International Journal of Religion Education and Law, 2025)
This research is aimed to find out is there any significant effect of using Instagram Media and Blended Learning towards students’ writing skill on the eleventh grade of MA Daar El Mu’minin in academic year 2020-2021. The population is the second-grade students of MA Daar El Mu’minin. The sample of the research is two classes. They are XI IPS 1 as the controlled class and XI IPS 2 as experimental class. It was conducted by using true experimental research design. The experimental group was taught by using Instagram Media and Blended Learning, while the controlled group was taught by using conventional learning using power point. The instrument was used to collect the data by writing a Descriptive text. After analysing the data, it was found that the value of wiring test using Instagram media t-test was t-count t-table (4.039 2.024) and for Writing using Blended learning was t-count t-table (4.182 2.024). it means that alternative hypotheses (Ha) were accepted and null hypotheses (Ho) were rejected. So, there is significant effects of using Instagram Media and Blended Learning towards students’ Writing skill.